(untitled) (Journal of the College of Basic Education, 2026)
The descriptive and analytical approach was adopted. The research sample consisted of 12 public schools in the Al-Rusafa II Directorate, comprising 30 geography teachers and 150 students with learning difficulties. The researcher used questionnaires to collect data, developing two questionnaires for teachers and students. The first questionnaire covered three topics: personal information, concept mapping strategies, and the role of teachers and administration in using concept maps and working with students with learning difficulties. The student questionnaire covered four topics: personal information, the availability of necessary tools for teaching geography, concept mapping strategies for working with students with learning difficulties, and the students’ benefit from concept mapping strategies. The most important findings were as follows: - Geography teachers used concept maps to implement educational tasks for students with learning difficulties. - Teachers implemented concept mapping strategies while being aware of the needs of learners with learning difficulties, employing teaching skills appropriate to their needs to ensure the success of the teaching and learning process. - Teachers utilize their abilities, knowledge, and experience through the use of concept mapping strategies to empower their students in geography. This strategy aims to equip learners with geographical scientific concepts and foster their scientific, intellectual, and creative skills. - No statistically significant differences were found at the 0.05 level of significance related to the variable of years of experience. Based on these findings, the researcher offered several recommendations and suggestions, including: - Educators and supervisors should monitor learners with learning difficulties at all educational levels to encourage the use of concept maps to reinforce and solidify their knowledge. - Teachers should be encouraged to complete training courses on how to implement modern teaching strategies to enrich the teaching process, particularly in geography.